2010
DOI: 10.1002/lsm.20927
|View full text |Cite
|
Sign up to set email alerts
|

Temporal heating profile influence on the immediate bond strength following laser tissue soldering

Abstract: Linear heating produced stronger bonds than step heating. The difference in the bond strength was more pronounced at high set-point temperatures and short dwell times. The bond strength could be increased with either higher set-point temperature or a longer dwell time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This temperature range is consistent with published data of laser tissue soldering of other tissues as well [ 6 , [66] , [67] , [68] ]. One study, Rabi et al, 2010 [ 59 ], demonstrated increasing bond strength with a series of rising temperatures up to 150 °C. Although they succeeded in providing bonding, this was an ex vivo study that measured only immediate bond strength and did not look at tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This temperature range is consistent with published data of laser tissue soldering of other tissues as well [ 6 , [66] , [67] , [68] ]. One study, Rabi et al, 2010 [ 59 ], demonstrated increasing bond strength with a series of rising temperatures up to 150 °C. Although they succeeded in providing bonding, this was an ex vivo study that measured only immediate bond strength and did not look at tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…It is only natural that automated and computerized systems should be incorporated in it. Rabi et al, 2010 [ 59 ], included in the review, used a thermal feedback control system. Future development to advance the LTS of the GI tract should continue to develop thermal feedback controls, as well as implement laser distance measurement and image analysis providing superior bonding due to the controlled environment.…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect is the lack of control on the temperature reached during soldering. Previous studies have shown that the strength of the tissue connection strongly correlates with the temperature profile . Dye‐enhanced LAVA is based on thermal heating involving localized absorption of laser light using chromophores.…”
Section: Introductionmentioning
confidence: 99%